Hinduísmo e Budismo em Max Weber: uma indologia sem orientalismos - Oliveira, Arilson Silva de (2016)
Those intellectuals in Western modernity who exempted themselves from the Orientalist intellectual vanguard position did so, in part and in fact, once they were deeply involved with Eastern philosophy (especially, the Indian); undeniably in greater number among the Germans. This German intellectual look, along with a clear indomania, remained almost completely apart from the imperialist exploratory justifications, so attractive to the British and the French minds, as Said’s Orientalists, those explored by literary dictates and other Orientalists presented by him. Therefore, we confirm and disagree, at the same time, with the author of Orientalism on a fundamental point: Germany has opposed orientalisms. One, to a lesser extent, based specifically on Hegel’s communicating vessels (coming from some English and French), which confirms Said’s thesis; the other, and here under the particular look of Max Weber, opposed to the imperialist and modernist Orientalism. Given this premise, we deal with a fruitful and broad intellectual understanding, under the Weberian look, with respect to the transmission of ideas that took place in the nineteenth and early twentieth centuries, the so-called East India towards West Germany. Nevertheless, we have the following central problems: what would Weber's interests be? What and how did he present the Indian religions? Was he a mere influencer of Orientalism, as Said claims? Another Eurocentric adventurer and rationalist when it comes to an oriental culture? About the the first two questions, our research points to deep intellectual interests on the part of the German, far beyond what was expected; on the other questions, the answer is notably negative, since Weber will go beyond his time in many respects and will have unprecedented concerns, conclusions and amplifications regarding the indological analysis. Besides, he was not oblivious and submissive to the reports and analyzes coming from England and France, much less to the rationalist European and modern dictates that propagate the idea of being "better" than other times and other cultures.